2014
DOI: 10.2478/intag-2013-0024
|View full text |Cite
|
Sign up to set email alerts
|

TDR technique for estimating the intensity of effective non rainfall

Abstract: A b s t r a c t. The objective of this paper is to present a method for determining diurnal distribution of the intensity of effective non rainfall water flux. It was found that the application of TDR technique for the determination of diurnal dynamics of effective non rainfall water flux requires temperature correction of sensed volumetric moisture contents. Without temperature correction the error of estimated non rainfall water flux can be as much as 26%. In addition, the effect of temperature changes on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The application of the TDR technique and the introduction of temperature correction ensures that soil moisture can be determined with high accuracy (up to 0.001 m 3 m -3 ). The method of determination of the temperature correction is elucidated in the papers by (Janik et al, 2014;Oates et al, 2017;Skierucha, 2009). When the LP/ms probe is placed horizontally, we found that it was possible to register the volume of soil moisture in the top soil layer (2 cm).…”
Section: Methodsmentioning
confidence: 94%
See 4 more Smart Citations
“…The application of the TDR technique and the introduction of temperature correction ensures that soil moisture can be determined with high accuracy (up to 0.001 m 3 m -3 ). The method of determination of the temperature correction is elucidated in the papers by (Janik et al, 2014;Oates et al, 2017;Skierucha, 2009). When the LP/ms probe is placed horizontally, we found that it was possible to register the volume of soil moisture in the top soil layer (2 cm).…”
Section: Methodsmentioning
confidence: 94%
“…However, due to varied weather conditions, the values of E P in the successive series were different. The values of E R were determined with the use of the knowledge of the dynamics of volumetric moisture of soil in isolated spaces (Janik et al, 2014). The application of the TDR technique and the introduction of temperature correction ensures that soil moisture can be determined with high accuracy (up to 0.001 m 3 m -3 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations